PENGARUH KOMPETENSI, PENGALAMAN, INDEPENDENSI, DAN MOTIVASI AUDITOR PADA KUALITAS AUDIT - Partha Nadi, I Made Putra; Suputra, I Dewa Gde Dharma (E-Jurnal Akuntansi, 2017)
Independent auditor is the party that provides services mainly in the field of auditing financiaing  statementses of a company goes increase the confidence users of audit reports that the company reported financial statements free of ingredient manipulation in reporting. This requires the auditor to consider audit quality it produces. This means that the end result will determine the quality of the audit of an auditor. To find out how the results of the audit required a reliable and terpecay auditor. This study used a questionnaire survey techniques. This nreaserch used populations or respondent’s it’s  90 pepople at auditors. The samples in this study with purposive sampling with a sample size that is used by 36 auditors. Analysis of the data used in this research is multiple linear regression analysis. The results of this research show that the competence, experience, independence and motivation auditor signifikans on audit quality.
Keywords: competence, experience, independence, motivation, audit quality